2010
DOI: 10.1260/0263-0923.29.4.281
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Vibration and Dynamic Stability of the Printing Paper Web with Variable Speed

Abstract: Parametric vibration and dynamic stability of the printing paper web with variable speed were studied. The speed of the moving paper web was regarded as the sum of the constant mean speed and the sine pulse speed. The dynamical model and the transverse vibration differential equation were established. The period coefficient state equation was obtained by discretizing the space variable of the differential equation with the differential quadrature method and imported state vector. The instability region and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…Discretization method of vibration equation DQM is used to solve equation (30). DQM [34][35][36] approximates the derivatives of the function at the given nodes by weighted sums of the function at the total nodes. The nodes are calculated by the following formula…”
Section: Dimensionless Differential Equation and Boundary Conditionsmentioning
confidence: 99%
“…Discretization method of vibration equation DQM is used to solve equation (30). DQM [34][35][36] approximates the derivatives of the function at the given nodes by weighted sums of the function at the total nodes. The nodes are calculated by the following formula…”
Section: Dimensionless Differential Equation and Boundary Conditionsmentioning
confidence: 99%
“…Li et al [40] reviewed the nonliner dynamic response of a membrane under impact load based on the perturbation method and von Kármán's large deformation theory. Free linear vibration properties and stability of a printing paper with variable velocity were discovered by Wu and coworkers [41]; it is shown that the amplitude of pulse speed had influence on the stable region, as well as unstable region of the web. In printing, a time-dependent velocity will affect the printing quality of a membrane, although few authors were attentive towards the effects of variable velocity of membranes on the nonlinear vibration.…”
Section: Introductionmentioning
confidence: 96%
“…As a complex vibration system, a crane is composed of several subsystems with inherent vibration characteristics [5,6]. The power train is an important source of vibration and the noise of crane, which is composed of power assembly, drive shaft and drive axle assembly [7].…”
Section: Introductionmentioning
confidence: 99%